Do democracies promote peace in the lights of democratic peace theory? - Balcı, Fatih (Journal of Human Sciences, 2011)
It is believed that democracy and peace are inextricably linked, that democracy leads to and causes peace, and that peace cannot be achieved in the absence of democracy. It is an obvious but important starting-point to remember that democracy and peace are not timeless but historical social concepts. Indeed, war itself is a historical product as the negation of peace. Democracy is accepted as the only way for the peaceful world according to the Democratic Peace Theory, but to understand the democratic peace theory, it will be better to ask the question, “What is democracy”? Democratic peace theory’s main argument is that democracies do not fight each other, but “what kind democracies”? In this paper some important points of democracy and the democratic peace theory will be pointed out. This paper gives a perspective of the relationship of democracy and peace, and clarifies the question of “does democracy really promote peace”?